Engineered nanomaterials: risk perception, regulation and insurance. Issue 4 (20th April 2016) - McAlea, Eamonn M.; Mullins, Martin; Murphy, Finbarr; Tofail, Syed A.M.; Carroll, Anthony G.
Abstract : Concerns surrounding the health risk of engineered nanomaterials, effective regulation and the lack of specifically tailored insurance products for the nanotechnology sector are putting the industry's long-term economic viability at risk. From the perspective of the underwriter, this article speculates on the relationship between risk perception, regulation and insurability. In the nanotechnology sector, regulators are currently failing to keep pace with innovation, and insurers generally lack guiding principles for underwriting occupational risk from nanomaterial exposure. Such vulnerabilities when combined with misguided risk perceptions can lead to the overpricing of risk transfer and ill-conceived regulatory initiatives, thus potentially exhausting resources and stifling innovation in the sector. In the absence of well-developed regulatory protocols, the insurance industry has, and will continue, to occupy a key role as an effective lobby in terms of improved risk management practice. We suggest that the insurance industry will increasingly rely on control banding frameworks and 'risk mitigation at source' methods developed in conjunction with their clients to manage severe acute diversifiable risks. Long tail risk will continue to represent a serious challenge to insurers and regulators. In the meantime, insurers will have to bridge their current needs with improvised solutions. As an example of one possible solution, we outline a framework that utilizes financial instruments to hedge an insurer's exposure to uncertain estimates of these long-term risks.